Comparative Analyses Concerning Triaxial Compressive Yield Criteria of Coal with the Presence of Pore Water. (3rd February 2020) - Liu, Rulin; Yu, Yanbin; Cheng, Weimin; Xu, Qingfeng; Yang, Haotian; Shen, Jialong
Abstract : The least absolute deviation is used as a metric to analyze the applicability of five yield criteria, to describe the yield characteristics of coal based on triaxial compressive strength tests on natural, water-saturated, and seepage coal samples with the presence of pore water. The results show that the strength of coal exhibits nonlinear characteristics with the increase of confining pressure, which the linear Coulomb criterion fails to authentically describe. Although the parabolic Mohr criterion can describe the nonlinearity feature more decently than the linear yield criterion, the fitting error is significant, and the uniaxial compressive strength of coal is overestimated. The Hoek-Brown criterion, quadratic polynomial criterion, and exponential criterion yield decent fitting quality for the coal rock. In particular, the exponential strength criterion can accurately reflect the actual uniaxial compressive strength of the rock. However, the differential principle yield stress for an infinite confining pressure calculated from the exponential strength criterion is lower than the measured value. Furthermore, by employing effective stress principle to analyze the yield criteria for the saturated and seepage coal samples, one can find that the quadratic polynomial criterion and the exponential criterion can also reflect the changes of yield characteristics during the fluid-solid coupling triaxial compression test.